Telegrams have been received from the following sources asking for intervention to save the lives of Santiago Alvarez and Sebastian Zapirain, two Communists who are under sentence of death in Madrid (list)
Telegrams have been received from the following sources asking for intervention to save the lives of Santiago Alvarez and Sebastian Zapirain, two Communists who are under sentence of death in Madrid: 1. Representatives of Spanish Solidarity, Women's Union, U.G.T., Spanish Communist Party, at Langogne. 2. Union of Spanish Women, Tarn Department. 3. Spanish Women's Meeting, Toulouse. 4. Seventeen doctors of Rosario, Argentina. 5. Committee of Aid for the Spanish People, Buenos Aires. 6. Local Workers Union, Rosario 7. U.G.T. Committee, Tarn Department. 8. French Women's Union 9. Frag, Pau. 10. Vincent Marti, Pau. 11. Committee France-Spain, Rhone Department. 12. National Committee of Spanish Women in France, Toulouse. 13. Committee for Aid of Spanish People, Bellville Cordoba. 14. Spanish U.G.T. members in Argentina. 15. Members of National Front, Loire et Cher Department. 16. Communist Party, Oloron, Lower Pyrenees. 17. Trades Council, Oloron. 18. Committee France-Spain, Oloron. 19. Committee France-Spain of the Young People, Aude Department. 20. Communist Railwaymen of Toulouse. 21. Five hundred French Republicans at Public Meeting at Vic Fezensac. 22. Spanish U.G.T. Special Meeting with representatives from all parts of France, Toulouse. 23. Spanish Women meeting at Toulouse. 24. C.G.T. Departmental Trades Council, Eastern Pyrenees. 25. Spanish Women's Meeting at Toulouse. 26. Tomas, for Spanish Republican Parties and Trade Union Organisation of Loire. 27. Political Organisations of Beaumont, Lomagne. 28. Spanish Women at Toulouse. 29. District (Oran) Committee of Unified Party of Catalonia. 292/946/1/46